2018
DOI: 10.1016/j.jacbts.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small Molecule to Increase Cardiomyocytes and Protect the Heart After Ischemic Injury

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…The precise mechanisms by which TT-10 promoted the hiPSCM proliferation were not analyzed in the present study. In a previous study [4], we revealed that TT-10 not only activated the YAP-TEAD axis, but also had crosstalk with Wnt signaling via mild inhibition of GSK3β. Furthermore, TT-10 upregulated nuclear factor erythroid 2-related factor 2 (NRF-2) and enhanced antioxidant responses in vitro.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The precise mechanisms by which TT-10 promoted the hiPSCM proliferation were not analyzed in the present study. In a previous study [4], we revealed that TT-10 not only activated the YAP-TEAD axis, but also had crosstalk with Wnt signaling via mild inhibition of GSK3β. Furthermore, TT-10 upregulated nuclear factor erythroid 2-related factor 2 (NRF-2) and enhanced antioxidant responses in vitro.…”
Section: Discussionmentioning
confidence: 80%
“…We identified a small molecule, TAZ-12, developed its fluorine substituent TT-10 ( Fig. 1A) and found that TT-10 strongly promoted the proliferation of rat neonatal CMs and activated CM cell division and that it could also potently activate CM cell division in murine hearts after MI [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that Mst1/2 inhibition and YAP induction induces cell proliferation in vitro and in vivo. Previous studies using XMU‐MP‐1 (Fan et al, ) and the YAP activator TT‐10 (Hara et al, ) showed increases in proliferation of hepatocytes, small intestinal epithelial cells, and cardiomyocytes following in vivo treatment with the compounds. It is understandable that these data may raise some concerns with regard to the possible development of tumours or cancers, following prolonged use of these compounds.…”
Section: Discussionmentioning
confidence: 93%
“…More recently, a compound, TT‐10 has been described that can induce YAP activity by directly enhancing the transcriptional activity of the YAP–TEAD complex, although the exact molecular mechanism is not completely described. This compound was able to induce cardiomyocyte proliferation both in vitro and in vivo, and treatment with TT‐10, albeit at very high dose, improved the cardiac phenotype in a mouse model of myocardial infarction (Hara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel drug named TT-10 was described that enhances YAP-TAZ activity, resulting in increased proliferation of murine CMs in vitro (Ito et al, 2019). Intraperitoneal injection of TT-10 in infarcted mice reduced infarct size, improved cardiac function, and increased the numbers of phosphorylated histone-3and Aurora B-positive CMs in the border zone (Hara et al, 2018). These results provide a perspective for pharmacological rather than genetic intervention in Hippo signaling to stimulate CM proliferation in injured hearts.…”
Section: Wnt Signalingmentioning
confidence: 84%